Titanic : the long night - Hoh, Diane; Copyright Paperback Collection (Library of Congress) (N.Y. : Scholastic, 1998)
During the final hours aboard the Titanic on her ill-fated voyage in 1912, the helpless passengers find out who will survive the long night.
Keywords: Movie novels